Prevalence of intestinal parasites versus knowledge, attitude and practices (KAPs) with special emphasis to Schistosoma mansoni among individuals who have river water contact in Addiremets town, Western Tigray, Ethiopia. - Alganesh Gebreyohanns; Melese Hailu Legese; Mistire Wolde; Gemechu Leta; Geremew Tasew (PLoS ONE, 2018)
BACKGROUND:Intestinal parasite infections are major public health problems in resource-limited countries that adversely affect the well-being of millions. Among these, intestinal schistosomiasis is a serious public health problem in tropical and sub-tropical countries. METHODS:A Community based cross sectional study was conducted from February to April 2017 in Addiremets town, Ethiopia. Socio-demographic associated risk factors and knowledge, attitude and practices of individuals regarding intestinal parasite infection including schistosomiasis were collected from 411 study participants using pretested structured questionnaires. From each study participant, a fresh stool sample was collected and direct microscopy, formol-ether concentration and Kato- Katz techniques were performed. Snails were checked and collected from the nearby study area river. The collected data was entered and analyzed using SPSS version 20. Bi-variant and multiple logistic regressions were used for correlation analysis. A P <0.05 was considered as statistically significant. RESULT:The overall intestinal parasite prevalence was 51.3% (211/411). The most prevalent parasites were S. mansoni 26.3%(108/411) and Hookworm 23.1%(95/411). The prevalence of intestinal parasites among males and females were 54.1%(131/242) and 47.3%(80/169) respectively. The highest proportion of parasite infection was reported among the age group of 5-9 year old participants, at 70.6%(36/51). The prevalence of S. mansoni was 26.3% (108/411) with mean infection intensity of 218 eggs per gram (range: 24 to 1728). Among study participants, 94.4% had good knowledge while 35.9% of them had poor practices towards intestinal parasite and Schistosomes infection prevention. CONCLUSION:High prevalence of intestinal parasitic infection was observed in Addiremets town and the most common parasites identified were S. mansoni and Hookworm. Most study participants had light infection intensity of Schistosomiasis, Ascariasis and Hookworm infection. Majority of the participants in the study area had good knowledge and positive attitude about intestinal parasitic infection and schistosomiasis control. Shells of Biomphalaria species, Bulinus species and Physa species were collected from the Mytsaeda river shore.